BRONCHIAL ASTHMA IN CHILDREN: A MODERN VIEW OF THE PROBLEM - Mirrahimova, M.H.; Khalmatova, B.T.; Tashmatova, G.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Bronchial asthma is one of the most common chronic diseases. Statistical indicators of the prevalence of asthma are based mainly on data obtained from the treatment of patients in medical institutions. However, information on the prevalence of bronchial asthma does not correspond to reality, as many patients for various reasons do not address to medical institutions. The parents of the children have a negative attitude towards diagnosing a chronic disease, and doctors often do not diagnose bronchial asthma, especially in the early stages of development and in cases of mild diseases. Thus, according to the Healthcare data of the Tashkent region, a number of patients, especially those with mild bronchial asthma, did not establish the correct diagnosis at all in the childhood period, and in a significant proportion of patients with moderate and severe asthma, the correct diagnosis was made with a delay of 2-6 years from the onset of the disease.